Robust machine learning based Intrusion detection system using simple statistical techniques in feature selection - Sunil Kaushik; Akashdeep Bhardwaj; Ahmad Almogren; Salil bharany; Ayman Altameem; Ateeq Ur Rehman; Seada Hussen; Habib Hamam (Scientific Reports)
Abstract There are serious security issues with the quick growth of IoT devices, which are increasingly essential to Industry 4.0. These gadgets frequently function in challenging environments with little energy and processing power, leaving them open to cyberattacks and making it more difficult to implement intrusion detection systems (IDS) that work. In order to address this issue, this study presents a unique feature selection algorithm based on basic statistical methods and a lightweight intrusion detection system. This methodology improves performance and cuts training time by 27–63% for a variety of classifiers. By utilizing the most discriminative features, the suggested methods lower the computational overhead and improve the detection accuracy. The IDS achieved over 99.9% accuracy, precision, recall, and F1-Score on the dataset IoTID20, with consistent performance on the NSLKDD dataset.